Permainan Mencari Huruf Yang Sama Dalam Meningkatkan Kemampuan Membaca Anak Usia Dini Melalui Media Papan Flanel - Ummi Hani Nasution; Siti Khadijah Azzahra; Keysa Zalia Amanda; Lidya Sofiana; Khadijah Khadijah (Jurnal Ilmiah Wahana Pendidikan, 2022)
One aspect of motor development that must be considered carefully when a child enters his teens is the maturation of his motor skills. The development of motor skills is often seen as evidence that a child is growing and developing healthily. Reading ability is one of the four components of linguistic skills. These four skills include listening comprehension, conversational fluency, reading comprehension, and writing fluency. desktop qualitative research was the method of choice for this study. Purposive sampling involves collecting data for a specific purpose rather than collecting data for the sake of it, as well as avoiding questions about sample size when determining research topics. The data collection methods used in this study included observation and interviews. In this flannel board game, children are told to learn how to play chili sauce, the child is asked to take some of the letters that are the same as those on the board after that the child says the letter is sambal. write back in their notebooks. So that children can understand the various letters. In spelling letters, children are told to read the letters on the flannel board, for example "Glasses" where children can follow them, so that children can read fluently. In Al-Ikhlas Kindergarten there are 13 children. There are some who have developed in reading and there are still children who have not experienced development.